دور المساجد في التعليم بالعراق خلال العصر العباسي الأول (Journal of Humanitarian and Applied Sciences, 2023)
Since the advent of Islam, mosques have played their religious role as the most appropriate place for people because they carry the trait of safety and worship. They also have the most important cultural institutes for the study of Islamic and Arab sciences, as well as many mental sciences, which were developed and diversified during the Abbasid era. The Prophet’s Mosque, may God’s prayers and peace be upon him, is the first Islamic cultural centre, followed by mosques that were established in the areas conquered by the Muslim Arabs, and played their religious and scientific role, and the most important centres of Arab Islamic civilization. However, the mosques that were established during the Abbasid era were noted for their attention by the early Abbasid Caliph as having scientific seminars. A message other than the religious message was delivered, and discussion councils were held among scholars, jurists and caliphs, sometimes discussing matters of religion, jurisprudence, hadith, literature and poetry. They often took place inside the mosque, absorbing large numbers of those who wanted to acquire the knowledge. The city of Baghdad became famous in the area of science, literature and jurisprudence throughout the Muslim world. The country of Iraq has become the focus of interest for many students seeking knowledge from all regions of the Islamic world, and mosques have played a social role that nurtures daily interests and organizes life between individuals and groups.